Hubungan antara Terpaan Media Luar Ruang Kawasan Tanpa Rokok dengan Persepsi Mahasiswa terhadap Kawasan Tanpa Rokok di Area Universitas - Muhammad Alfian Khairul Alam; Muhammad Ramdhani (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to analyze the relationship between exposure to outdoor media on Smoke-Free Areas (Kawasan Tanpa Rokok/KTR) and students’ perceptions within the university environment. The study employs a quantitative approach with an associative research design involving 189 respondents selected through a non-probability sampling technique. Data were collected using a Likert-scale questionnaire. Data analysis includes validity, reliability, and normality tests, as well as Pearson correlation and simple linear regression as a supporting analysis. The results indicate a significant relationship between outdoor media exposure and students’ perceptions, with a correlation coefficient of 0.529, which falls into the moderate category. Hypothesis testing shows that the calculated t-value (8.516) is greater than the t-table value (1.973) with a significance level of 0.000 < 0.05. The findings suggest that higher levels of outdoor media exposure are associated with more positive student perceptions toward the implementation of smoke-free area policies.